Australia First Party - Australia First Party (Rockdale, N.S.W. : Australia First Party, 2005)
"The website has been created to serve the needs of a new generation of nationalists in Sydney"--Title screen.
Title from title screen (viewed on 27 November, 2006).
Text and graphics.
Mode of access: Internet via World Wide Web. On 27/11/2006 available from Australia First Party website at: http://ausfirst.alphalink.com.au
Selected for archiving
Keywords: Australia First Party; Elections -- New South Wales; Political campaigns -- New South Wales; Political parties -- New South Wales